(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
Persicaria lankeshanensis, a new species of Polygonaceae from the Lankeshan Nature Reserve, Guangdong province of China, is described and illustrated. Persicaria lankeshanensis is similar to P. taquetii but differs from the latter by having stems, leaves, and ocreae densely pubescent, pedicels shorter than bracts, smaller flowers and achenes, and achenes opaque and minutely granular-striate. A comparison of achenes, pollen and abaxial leaf epidermis between the two species is provided. DOI: http://dx.doi.org/10.3329/bjpt.v21i2.21353 Bangladesh J. Plant Taxon. 21(2): 147-152, 2014 (December)